Suggested Land Use and Afforestation of Wasteland in The North- Eastern Part of The Aravalli Hill Gaps - Raghav, K S (Annals of Arid Zone, 2016)
The paper embodies the results of studies carried out on quaternary geology, geomorphology and desertification in the north-eastern part of Aravalli hill gaps around Sambhar salt lake in Rajasthan. The dominant landscape feature is the superimposition of earlier humid landscape by later aeolian deposits in semi-arid to arid climates. The area is facing environmental problems due to sand accretion, soil. salinisation. soil erosion, flooding and water logging. These are the products mainly of erosional and depositional processes accentuated by overgrazing, deforestation, engineering constructions and unplanned cultivation on the dune tops.